2019
DOI: 10.1080/1331677x.2019.1689837
|View full text |Cite
|
Sign up to set email alerts
|

Self-employment and unemployment relationship in Romania – Insights by age, education and gender

Abstract: We check on the short term if self-employment in Romania influences unemployment and vice versa. Age, education and gender characteristics treat both variables, and self-employment considers both cases with and without employees. The objective is to look at the job creation and unemployment reduction in quarterly variation during the 1999Q1-2017Q3 period. On autoregressive models, we apply the Toda and Yamamoto (1995) procedure, detailed by Giles (2011), to assess for Granger Causality. We found for unemployme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…All participants noted that OTPDPs in STEM education helped teachers develop the skills that would make them more likely to be employed in the future. Research has also shown that STEM education positively affects employment (Grigorescu et al, 2020;Mattoo et al, 2008) because teachers who receive STEM education are more likely to meet job requirements (Thomas & Lonobile, 2021). Teachers who receive STEM education do not need occupational mobility because they meet job requirements much more than those who do not receive STEM education (Yang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…All participants noted that OTPDPs in STEM education helped teachers develop the skills that would make them more likely to be employed in the future. Research has also shown that STEM education positively affects employment (Grigorescu et al, 2020;Mattoo et al, 2008) because teachers who receive STEM education are more likely to meet job requirements (Thomas & Lonobile, 2021). Teachers who receive STEM education do not need occupational mobility because they meet job requirements much more than those who do not receive STEM education (Yang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One dimensions of the education system is to provide to the scholars and students the needed skills to can easy integrate into the labour market. Cultivating an entrepreneurial behavior and thinking represents one of the goal of the education system in Romania in the last three decades, self-employment being a tool of keeping the unemployment away [10].…”
Section: Problem Statement and Methodologymentioning
confidence: 99%
“…According to Grigorescu et al (2019), unemployment is an effective inclusion tool for some vulnerable groups but ineffective for others. Employee-based self-employment has a lower diversification, showing a strong risk aversion and a poor start-up effect.…”
Section: Literature Reviewmentioning
confidence: 99%